A Eksklusivitas, Keunikan dan Antitesis Pemberitaan Salib Kristus dalam Perspektif 1 Korintus 1:18-25 - Manuputty, Mozes; Gulo, Refamati; Refamati Gulo (STT Pelita Dunia, 2024)
Abstract: The message of the Cross of Christ and its proclamation is an urgent part of Biblical theology. The message of the Cross emphasizes the incarnate status of Jesus (John 1:14) or the humble status of Jesus in the “form” (Yun. MORPHE) of a servant (Yun. DOULOS), and being made in the likeness of men (Phil. 2:7). Without the incarnation of Jesus, there is no teaching about the Cross of Jesus in the Bible. This study aims to explore in depth Paul's thoughts on the meaning of the preaching of the cross of Christ, how his views provide significant theological insights for human life. The method used is qualitative with an exegetical analysis approach. The results of this study show that the exclusivity, uniqueness and antithesis of the preaching of the Cross of Christ in the perspective of 1 Corinthians 1: 18-25 is the only way of salvation according to Christian teaching and contains absolute truth about salvation. Thus, the message of the cross was understood and accepted by the early church and its relevance for Christians today.